Drainage system research and application of deep coalbed methane gas reservoirs in Daning-Jixian block - Ming CHEN; Dameng WANG; Lizhu YU; Junyi SUN; Xin FENG; Kang ZHANG; Xianfeng GU; Liwei WANG; Zesong YIN; Huan ZHANG (Meitan xuebao)
Compared to Medium-shallow coalbed methane, deep coalbed methane exhibits significant differences in occurrence state, production mechanism, lifting technology, etc.As an important part of coalbed methane development, drainage directly impact the gas production of deep coalbed methane wells. Therefore, it is essential to explore a refined drainage system that is suitable for deep coalbed methane. Based on the geological conditions and reservoir properties of the Daning-Jixian block, isothermal adsorption tests were conducted on the main producing layer-coal seam No.8 to analyze the gas content and occurrence state of deep coalbed methane. Considering the gas well production laws and supporting gas extraction processes, the research also analyzes dynamic production data from 29 deep coalbed methane wells，preliminarily divides the production stages of deep coalbed methane wells, and further demonstrates the main tasks and production characteristics of different stages. Combining the development theory of "artificial gas reservoirs" and the design concept of a production system for the entire life cycle of gas wells, the research divides the entire life cycle of gas wells into 5 production stages and forms a standard template. Moreover, field experiments were conducted to produce according to the designed refined drainage system and evaluate the applicability of drainage system for deep coalbed methane wells. Research results indicate: ① No.8 coal seam is generally stable. Isothermal adsorption experiments show that the Langmuir volume is generally greater than 20 m3/t, Langmuir pressure is greater than 2.8 MPa, and gas saturation in deep coal seams increases by 29.6% compared to medium-shallow layers, mainly existing in a saturated to supersaturated state, with free gas content reaching up to 20%−30%; ② Utilizing the coal-rock Langmuir curve and changes in curvature, the research figures out start-up pressure, inflection pressure, and sensitivity pressure as 8−10 MPa, 5−7 MPa, and 2−3 MPa respectively. Furthermore, through the normalization of production time and horizontal segment length from 29 gas wells’ dynamic production data, the research preliminarily identifies that deep coalbed methane have gone through 4 production stages, with Stage I being post-fracture flowback, Stage II characterized by rapid initial production, Stage III focusing on exploring rational production allocation, and Stage IV indicating a decrease in gas production. The pressure, gas production, liquid production, and flowback rate parameters at each stage of the gas wells were also delineated; ③ Based on the objective laws of gas well production throughout its life cycle, with pressure control as the core, the research also divides the production stages of deep coalbed methane wells into 5 stages: flowback stage, initial production stage, stable production stage, decreasing production stage, and low production stage， with quantifying the control indicators and technical limits for each stage. The low production stage is awaiting further verification; ④ The average stable production time for 4 test wells has reached 360 days, far exceeding the average level of the pilot wells, with an average annual production of 33.279 million cubic meters from the day of self-gas production, accumulating a high increase of 71.35%. That proves good adaptability of the refined drainage system in the Daning-Jixian block.